2018 IEEE 4th World Forum on Internet of Things (WF-IoT) 2018
DOI: 10.1109/wf-iot.2018.8355116
|View full text |Cite
|
Sign up to set email alerts
|

Extending the battery lifetime of wearable sensors with embedded machine learning

Abstract: Smart health home systems and assisted living architectures rely on severely energy-constrained sensing devices, such as wearable sensors, for the generation of data and their reliable wireless communication to a central location. However, the need for recharging the battery regularly constitutes a maintenance burden that hinders the long-term cost-effectiveness of these systems, especially for health-oriented applications that target people in need, such as the elderly or the chronically ill. These sensing sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 33 publications
0
36
0
Order By: Relevance
“…However, it should be noted that this was a biaxial rather than triaxial accelerometer, and that a fairly limited subset of features (no spectral features) were used, so it is difficult to draw a solid conclusion from this single study. More recent works also demonstrate that simple classification tasks can be effectively conducted at very low sampling frequency and resolution, increasing the battery lifetime of wearable sensors by more than an order of magnitude [49]. Khan et al [50] performed a comprehensive study on optimising the sampling frequency of accelerometers in the context of human activity recognition.…”
Section: Accelerometer Selection and Configurationmentioning
confidence: 99%
“…However, it should be noted that this was a biaxial rather than triaxial accelerometer, and that a fairly limited subset of features (no spectral features) were used, so it is difficult to draw a solid conclusion from this single study. More recent works also demonstrate that simple classification tasks can be effectively conducted at very low sampling frequency and resolution, increasing the battery lifetime of wearable sensors by more than an order of magnitude [49]. Khan et al [50] performed a comprehensive study on optimising the sampling frequency of accelerometers in the context of human activity recognition.…”
Section: Accelerometer Selection and Configurationmentioning
confidence: 99%
“…Other approaches, orthogonal to those aforementioned, study the on-board calculation of the feature extraction stage of activity recognition systems. In [14][15][16][17][18][19], it was shown that calculating features on the wireless sensor nodes could reduce the energy consumption of their wireless transceivers or flash memories due to the reduced amounts of data.…”
Section: Related Workmentioning
confidence: 99%
“…[28][29][30]. Since this stage often drastically reduces the data rate, as a relatively small number of features is calculated from a large number of samples of a window, it was subject to a lot of research to perform this stage as near to the sensor as possible, i.e., on board of a wireless sensor node [14][15][16]18,19], or even on-sensor [17,21]. However, each application-specific setup varies in sensor sampling frequency, sliding window size, sliding window overlap, and number of features and their computational effort in calculating them.…”
Section: Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work investigated downsampling data packets as a method for reducing the transmission data rate without compromising machine learning classification accuracy. In [16], large amounts of redundant accelerometer data packets were found, which motivated the approach in [17] to uniformly downsampling accelerometer data in both sampling frequency and bit depth. A reduction of recorded measurements by three orders of magnitude improved battery life from weeks to years without compromising classification accuracy [17].…”
Section: Introductionmentioning
confidence: 99%